N-glycosylation controls inflammatory licensing-triggered PD-L1 upregulation in human mesenchymal stromal cells - Strauch, Vivien; Saul, Domenica; Berisha, Mirjeta; Mackensen, Andreas; Mougiakakos, Dimitrios; Jitschin, Regina (Stem Cells, 2020)
Mesenchymal stromal cells (MSCs) are characterized by their multipotency, regenerative potential, and immunoregulatory properties. Nowadays, MSCs represent a promising cell-therapeutic option for hyperinflammatory conditions such as graft-vs-host disease following allogeneic hematopoietic stem cell transplantation. A better understanding of their biology is a prerequisite for improving their treatment efficacy. Emerging evidence suggests that immunosuppressive properties are not constitutively active in MSCs. Instead, microenvironmental inflammatory stimuli such as the cytokines interferon (IFN)-γ or tumor necrosis factor (TNF)-α license MSCs to acquire a tolerance-promoting phenotype. The immunological checkpoint molecule programmed death-ligand 1 (PD-L1) is an important regulator of T-cell responses. Binding of PD-L1 to the programmed cell death protein 1 (PD-1) receptor on T cells suppresses their activation, proliferation, and induces apoptosis. Previous studies have revealed that cell surface expression and secretion of PD-L1 are part of the MSCs' immunomodulatory armamentarium. Here, we report that inflammatory licensing leads to an enhanced PD-L1 cell surface expression and secretion, which are both accompanied by an increased posttranslational protein N-glycosylation. These post-translational modifications have been shown to be critical for key biological processes such as cell trafficking, receptor signaling, and immunohomeostasis. In fact, promoting N-glycosylation in MSCs yielded increased PD-L1 levels. We report for the first time that PD-L1 N-glycosylation plays a decisive role for its transport to the MSCs' cell surface and its subsequent secretion (in response to proinflammatory trigger). Our data offer insights into a novel regulatory mechanism with the potential to be exploited as a means to foster the immunosuppressive potency of human MSCs. © AlphaMed Press 2020 SIGNIFICANCE STATEMENT: Mesenchymal stromal cells (MSCs) possess immunoregulatory properties and are hypoimmunogenic. These characteristics of MSCs make them promising candidates for cell therapeutic approaches in hyperinflammatory conditions such as graft-vs-host disease following allogeneic stem cell transplantation. This study shows that inflammatory stimuli promote expression and secretion of PD-L1 in human MSCs. It reveals for the first time that this adaptive process is accompanied by an enhanced N-glycosylation, which is a prerequisite for PD-L1 to be transported to the cell surface and to be secreted. Therefore, promoting N-glycosylation could be explored as a means to improve the MSCs' therapeutic efficacy.
EVALuna2:216179

N-glycosylation controls inflammatory licensing-triggered PD-L1 upregulation in human mesenchymal stromal cells - Strauch, Vivien; Saul, Domenica; Mackensen, Andreas; Jitschin, R.; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Regulation of immunological checkpoints in human mesenchymal stromal cells - Strauch, Vivien; Saul, D.; Mackensen, Andreas; Jitschin, R.; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02